Reproducibility assessment among three methods for determining skeletal maturation in patients from 06 to 16 years (Research, Society and Development, 2020)
A cross-sectional, quantitative study was carried out through direct documentation in order to assess the efficiency of reproducibility between three methods of skeletal maturation in patients aged 6 to 16 years. The sample consisted of 63 individuals, attended at the Clinical School of the Department of Dentistry, on Campus I of the State University of Paraíba, 31 of whom were female and 32 male, who had 03 radiographic exams analyzed: lateral norm radiography, radiography panoramic and carpal radiography. In the studied sample, the average dental age (115.81 months) was lower than the average chronological age (122.70 months) for both sexes. Regarding bone age, in both sexes, the mean obtained (120.98 months) was close to the mean chronological age. The cervical vertebrae maturation indexes showed results similar to the dental and bone ages. It is concluded that the methods that present greater efficiency and reproducibility are those of analysis of dental age through panoramic radiography and bone age through carpal radiography. The analysis of the maturation of the cervical vertebrae by lateral lateral teleradiography shows, therefore, less sensitivity and less accuracy in its applicability.